EDUKASI SERTA MENGANALISIS TENTANG POSISI KERJA DI DINAS KESEHATAN KABUPATEN BERAU - Muhammad Mufti Fajrillah; Arys Hasta Baruna (Rena Cipta Mandiri, 2026)
Occupational Safety and Health (OSH) is an essential aspect of creating a safe, healthy, and productive work environment. Employees who perform work activities in a prolonged sitting position are at risk of developing musculoskeletal disorders due to poor ergonomic posture, particularly in the neck, shoulders, and back regions. This community service program aimed to improve employees’ knowledge of ergonomic working postures and the prevention of musculoskeletal disorders through stretching and strengthening exercises. The activity was conducted at the Berau District Health Office and involved 10 employees. The methods included observation, interviews, completion of the Nordic Body Map (NBM) questionnaire, educational sessions using posters and presentations, and demonstrations of stretching and strengthening exercises. The results showed that the participants consisted of 70% females and 30% males. Most employees worked in non-ergonomic postures, particularly when using laptops with screens positioned too low. Reported complaints included upper back pain in 40% of respondents and lower back pain in 20%, while 40% reported no complaints. Based on the NBM assessment, 70% of respondents were categorized as having mild musculoskeletal complaints, whereas 30% reported no musculoskeletal disorders.